Hungarian Monitoring, 24 June 1989 . [Magyar rádiófigyelő], 1989. június 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - US takes negative view of Soviet-Iranian rapprochement - West makes political and economic gestures in honor of changes in Hungary - Soviet Muslims and Iranian leaders - On the Polish Greens' conference Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) Central Committee session: personnel changes - Hungarian Democratic Forum (MDF) forms as a party - KDNP wants to operate as a political opposition group - Hungarian Socialist Workers' Party (MSZMP) Central Committee instigates investigation against Csaba Tabajdi - Anna Kéthly's ashes to be brought home next year - Károly Grósz: should he stay or should he go? Economy: - US wants to join with Japan in helping Hungary Külpolitika: - Az Egyesült Államok rossz szemmel nézi a szovjet-iráni közeledést - A Nyugat politikai és gazdasági gesztusokkal honorálja a magyarországi változásokat - A szovjet muzulmánok és iráni vezetők - A lengyel zöldek tanácskozásáról Belpolitika: - MSZMP KB ülés: személyi változások - Párttá alakul a Magyar Demokrata Fórum - Ellenzéki politikai szervezetként kíván működni a KDNP - Tabajdi Csaba ellen vizsgálatot indít az MSZMP KB - Jövőre haza hozzák Kéthly Anna hamvait - Grósz Károly: menjen, vagy maradjon? Gazdaság: - Az Egyesült Államok Japánnal összefogva kívánja segíteni Magyarországot